2020
DOI: 10.3390/jcm9092905
|View full text |Cite
|
Sign up to set email alerts
|

Key Strategies to Optimize Outcomes in Mild-to-Moderate Ulcerative Colitis

Abstract: Mesalamine (5-ASA) is the mainstay therapy in patients with mild-to-moderate active ulcerative colitis (UC). However, non-adherence to therapy and practice variability among gastroenterologists represent long-standing barriers, leading to poor outcomes. Additionally, targets to treat in UC are increasingly evolving from focusing on clinical remission to achieving endoscopic and histological healing. To date, systemic steroids are still recommended in non-responders to 5-ASA, despite their well-known side effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 95 publications
0
20
0
Order By: Relevance
“…This comprehensive systematic review and meta-analysis has demonstrated the efficacy and safety of oral Pentasa for the treatment of active mild-to-moderate UC. With therapeutic aims in UC becoming more ambitious, targeting endoscopic and histological remission as well as symptomatic improvement, there is increasing emphasis on optimizing currently available treatments and identifying patients who could benefit from dose escalation 46 . The multiple formulations of Pentasa provide physicians' with the scope for optimizing patients' 5-ASA dosing and thus impact not only the likelihood of symptomatic improvement and remission, but also treatment adherence, quality of life, and longterm outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This comprehensive systematic review and meta-analysis has demonstrated the efficacy and safety of oral Pentasa for the treatment of active mild-to-moderate UC. With therapeutic aims in UC becoming more ambitious, targeting endoscopic and histological remission as well as symptomatic improvement, there is increasing emphasis on optimizing currently available treatments and identifying patients who could benefit from dose escalation 46 . The multiple formulations of Pentasa provide physicians' with the scope for optimizing patients' 5-ASA dosing and thus impact not only the likelihood of symptomatic improvement and remission, but also treatment adherence, quality of life, and longterm outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Nonadherence arises from many factors such as a patients' fear of side effects or different drug routes, to name a few. For example, topical therapy with suppositories/enemas used with corticosteroids and 5-ASAs has been associated with increased nonadherence over oral therapies [ 32 ]. Therefore, IBD being complex disease may require diverse and mutually interacting components.…”
Section: Current Interventions To Ibdmentioning
confidence: 99%
“…10 The main approaches used for optimisation of 5-ASA are the use of combined oral plus rectal therapy and maximising oral doses. 10 A number of studies have shown that these approaches can increase the effectiveness of 5-ASA therapy. [11][12][13] A further step in 5-ASA optimisation has been the use of once daily dosing, which has demonstrated equivalent efficacy to divided dosing regimens and can improve patient adherence to treatment.…”
Section: What Are the New Findings?mentioning
confidence: 99%